Fatores de risco para depressão em pacientes que necessitam de cirurgia ortognática - Vicentini, Grasielle (2020)
The aim of this study was to evaluate clinical, psychosocial and genetic risk factors for depression in individuals with dentofacial deformities (DFD) who require orthognathic surgery. A transversal study was performed in 143 individuals with Class II and III skeletal malocclusion requiring orthognathic surgery. All patients were diagnosed for depression, chronic pain, somatization and temporomandibular disorders (TMD) according to the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD). The DNA was obtained from buccal cells. Genetic polymorphisms in DRD2 (rs6275 and rs6276) and ANKK1 (rs1800497) were genotyped using real-time PCR. Data were analyzed using the SPSS program (IBM, USA) v.23.0 and a significance level of 0.05 was considered. The prevalence of depression was higher in female patients and with vertical excess of the maxilla (p <0.05). The diagnosis of depression was associated with chronic pain, somatization and myofascial pain (p <0.05). There was no association between depression and the other TMD groups, and for genetic polymorphisms (p> 0.05). We concluded that the female gender, vertical excess of the maxilla, chronic pain, somatization and myofascial pain are risk factors for depression in patients with dentofacial deformity who require orthognathic surgery.